The Illusion of Consumer: Ads Influence for Agent of Intelligence - Muhammad, Vercia (JURNAL KOMUNIKASI INDONESIA, 2023)
This article will description influence pattern from ads, with saw case an agent of Central Intelligence Agency (CIA) namely Aldrich Hazen Ames. Ames arrested because information selling to other parties (double agent) for making money. The author assumed that his act influence by ads. Therefore the Jaguar XJ6 Sovereign car ads that driven by Ames at arrest used for sample. The author using Roland Barthes semiotics theory with explain meaning of denotative, connotative, and myth on the Jaguar car ads and then related with Jean Baudrillard concept. The method used is descriptive method, its is a method that makes systematically, factual, and accurate, characteristics and relationships of the phenomena studied. By using this method, the author analysis and observe of sign, describe every meaning on ads Jaguar that influence Ames (agent of CIA). The result that, the Jaguar car ads has influencing Ames become consumers illusions, that effect at consumerist acts. This act driving to high lifestyle (e.g. celebrity, hollywood) for obtain a social position, status, and prestige (sign value). For Baudrillard, this is fundamental elements in a capitalist society, there is a social and cultural significance in consuming the product which he calls sign value.